Effects of different anesthetic depth during propofol anesthesia on postoperative recovery 24 h after arthroscopic day surgery: A randomized clinical trial - Ning, Meng; Sun, Yue; Zhang, Hao; Chen, Caiyun; Sun, Linglu; Chen, Lijian; Xia, Zhengyuan; Lu, Yao (Frontiers in Pharmacology, 2022)
Background: This study aimed to compare the effects of different depths of sedation during propofol anesthesia on postoperative recovery 24 h after knee arthroscopy day surgery in adult patients. Methods: This prospective randomized controlled trial involved 126 patients (ASA physical status 1–2) who were scheduled to undergo arthroscopic day surgery. Patients were randomly divided into two groups: the light-sedation (L-Group) or deep-sedation (D-Group). In the L-group, the bispectral index values were kept in the range of 50–59; in the D-group, the bispectral index values were maintained in the range of 40–49. The Quality of Recovery-15 (QoR-15) score assessed 24 h postoperatively using a 15-item questionnaire was the primary outcome. Secondary outcomes included Athens Insomnia Scale scores, postoperative pain scores, nausea or vomiting. Results: The total QoR-15 score 24 h postoperatively was similar in the two groups (L-group median:130, IQR [127–132] vs. D-group median:131, IQR [126–135], p = 0.089). But among the five dimensions of the QoR-15, physiological comfort was significantly better in the D-group than L-group (p < 0.001). The time to open eyes (p < 0.001), follow the command (p < 0.001) and to extubation (p < 0.001) after surgery in the L-group were shorter than the D-group. The Athens Insomnia Scale scores (p < 0.001) and incidence of dreaming (p = 0.041) at the first postoperative night in the L-group was significantly higher than those in the D-group. Propofol consumption in the L-group was less than D-group (p < 0.001). Conclusion: For patients undergoing arthroscopic day surgery, general anesthesia with high-bispectral-index (50–59) cannot improve the total QoR-15 score 24 h postoperatively after surgery, but can lessen propofol consumption, reduce the time of extubation and anesthesia recovery period, compared with low-bispectral-index (40–49). Patients exposed to general anesthesia with low-bispectral-index values (40–49) may have better quality sleep and physical comfort than those with high-bispectral-index values (50–59). Clinical Trial Registration:http://www.chictr.org.cn/showproj.aspx?proj=126526, identifier ChiCTR2100046340